The Effect of PJU Quality, Environmental Security, Infrastructure Accessibility On Income Through Digital Innovation of MSMes in Balikpapan - Yusri; Etty Soesilowati; Hadi Sumarsono (PT. Maju Malaqbi Makkarana, 2026)
This study aims to analyze the effect of Public Street Lighting (PSL) Quality, Environmental Safety, and Infrastructure Accessibility on MSME Income through Digital Innovation in Balikpapan City. A quantitative approach with an explanatory research method was used on a sample of 100 MSME actors selected using purposive sampling. The data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results of the study prove that Digital Innovation plays a significant mediating role. The quality of PJU, Environmental Safety, and Infrastructure Accessibility have a positive and significant effect on Digital Innovation, which in turn directly increases MSME Income. These findings underscore that improvements in physical infrastructure and environmental safety create an ecosystem conducive to the adoption of digital technology by MSMEs, which is a major catalyst for improving their economic performance. The implications of this study suggest the need for integrated policies that combine the development of smart public infrastructure (smart street lighting) with digital literacy and access programs for MSMEs in order to promote inclusive and sustainable local economic growth